Secure Client- Server Based Remote Process Control - Hussain, Mohamed Abdullah; El-Mukhtar, Mumtaz Mohamed Ali; Ali, Wrya Mohamed (Sulaimani Journal for Pure and Applied Sciences, 2008)
Internet based process control has been in the focus in the past years due to the wide horizons it opens to the industry field, office and home automation. Simplicity (in hardware, software and the required resources) in any system is an asset to have. Especially, in our region in which we lack hardware and software company dealers and a lot of automation resources. It is best to depend on free software as far as is possible in addition to on simple easy repairable systems. In this research a hardware interface circuit and a software system has been designed to control the temperature and level of a liquid tank (water has been considered in our case study). The main advantage of the designed interface circuit is its simplicity and low cost. The same can be true for the software system in which we used Java servlet to accomplish the communication task. Java servlets have many advantages over the Common Gateway Interface (CGI) based methods used previously that has common problems of speed and data persistence. In security aspects a password has been added to all control action commands to secure our process control tasks. In addition to the security introduced by using Dynamic Domain Naming System (DYNDNS) servers that allows the use of dynamic Internet Protocols (IP) for accessing information on the Internet. The designed hardware and software systems could be used for remote or local control with no amendment and for both manual and automatic control. The system could be used with no need to have a public IP for both client and server.
Keywords: Network based instruments control; Remote process; Internet based processcontrol